TEACHERS’ PERCEPTIONS OF THE LEADERSHIP TO TK PAGARAN TAPAH DISTRICT DARUSSALAM ROKAN HULU - Anugrahwati, Tri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Every organization, including school certainly has a vision and mission. Inachieving the vision and mission have to be supported by the ability of a leaderwho not only lead, but also should have the competence and in accordance withhis position as a leader. This is consistent with the fact that leaders who succeedare those who have the ability and drive themselves to the objectives of theinstitution he leads. Phenomenon which is discovered in kindergarten in PagaranTapah Darussalam Rokan Hulu such as(1) the presence of some principals who donot want to work on improving the ability of educational personnel in improvingteacher performance, when there are seminars held outside the school, (2) themost principals do not have a good ability in cooperating with the teacher, (3) theprincipals who are less able to manage the facilities and infrastructure of existingschools, (4) the principal who did not want to attend a meeting at school andoutside school, and asked his representative to attend the meeting. The purpose ofthis study is to investigate teachers' perceptions of the leadership of TK. The studywas descriptive, which used quantitative as the technique of collecting file.Collection used questionnaire approach. The number of samples in this studywere33teachers. Based on the results of data processing, obtained a description ofthe leadership of the head teacher's perception TK in Pagaran Tapah DarussalamRokan Hulu in terms of indicators(1) leadership oriented to the duties of 49,62%,(2) leadership oriented to the relationship between humans by 58,71%. Thus, itcan be concluded that the perception of the leadership of the head of thekindergarten teachers are pretty good.Keywords: perceptions of teachers, principals Leadership